1992
DOI: 10.1159/000243747
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Levels in Amniotic Fluid from Women with Normal and Neural Tube Defect Pregnancies

Abstract: We analyzed nutrient levels in amniotic fluid obtained during the second trimester of normal, uncomplicated pregnancies from 221 women who delivered apparently healthy infants and from 8 with neural tube defect (NTD) pregnancies. Folate was measured by microbiological assay, vitamin B12 by a radiobinding method, and zinc, copper and iron by atomic absorption spectrophotometry. We found that the mean amniotic fluid nutrient levels of normal pregnancies were 24.7nmol/l for folate, 600pmol/l for vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 7 publications
5
27
0
Order By: Relevance
“…We detected cobalamin and folate concentrations in AF that are similar to concentrations previously reported by others [11,[35][36][37][38]. The cobalamin content was substantially higher than in serum from term newborns and mothers [39].…”
Section: Concentrations Of B Vitamins and Metabolitessupporting
confidence: 89%
See 1 more Smart Citation
“…We detected cobalamin and folate concentrations in AF that are similar to concentrations previously reported by others [11,[35][36][37][38]. The cobalamin content was substantially higher than in serum from term newborns and mothers [39].…”
Section: Concentrations Of B Vitamins and Metabolitessupporting
confidence: 89%
“…The cobalamin content was substantially higher than in serum from term newborns and mothers [39]. We observed a reduction in both B vitamins according to gestational age, as has previously been reported [38,40].…”
Section: Concentrations Of B Vitamins and Metabolitessupporting
confidence: 82%
“…Several clinical studies indicate that folate concentrations in postpartum serum and red blood cells are lower among women who have previously had a child with an NTD [28][29][30] ; however, there have been conflicting results, with some studies failing to find such an association [31][32][33][34][35] . Whether it is a low maternal intake or altered absorption/metabolism of folate that is responsible for the observed association with NTD risk has yet to be established 36 .…”
Section: Folic Acid Prevents Neural Tube Defectsmentioning
confidence: 99%
“…This controversy has been the subject of a recent review, in which it was concluded that there are moderate associations between low maternal B12 and an increased risk of NTDs (Ray and Blom, 2003). Other studies also indicate that B12 concentrations appear modified internally across the placenta, where a lower B12 status may or may not be present in serum, but is significantly lower in the amniotic fluid of NTD case versus control mothers (Gardiki-Kouidou and Seller, 1988;Weekes et al, 1992;Dawson et al, 1998;Steen et al, 1998;Suarez et al, 2003b). Additionally, Afman et al (2002) studied five SNPs in the coding region of the transcobalamin 2 (TCN2) gene, but none of the SNPs were associated with a significantly increased risk for NTDs.…”
Section: Vitamin B12mentioning
confidence: 99%